Pengaruh Work-Life Balance dan Budaya Kerja Terhadap Kinerja Karyawan PT. PLN (Icon+) Icon Plus Madiun - Ramadhan, Ahmad Dani; Puspasari, Aprilia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of work-life balance and organizational culture on employee performance at PT. PLN (ICON+) Icon Plus Madiun. Employee performance is a crucial factor in achieving organizational goals, influenced by the balance between work and personal life as well as the prevailing organizational culture. The research employed a quantitative method with an associative approach. Data were collected through Likert-scale questionnaires distributed to all 36 employees using a saturated sampling technique. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination with the help of SPSS version 25. The results indicate that work-life balance has a positive and significant effect on employee performance (t = 3.001; sig. 0.005), and organizational culture also has a positive and significant effect (t = 4.219; sig. 0.000). Simultaneously, both variables significantly influence employee performance (F = 85.215; sig. 0.000) with an R² value of 0.698. This means that 69.8% of the variation in employee performance is explained by these two variables, while the remaining 30.2% is influenced by other factors not examined in this study.